Anti-inflammatory Effects of Cardamonin in Ovarian Cancer Cells Are Mediated via mTOR Suppression - Chen, Huajiao; Shi, Daohua; Niu, Peiguang; Zhu, Yanting; Zhou, Jintuo (Planta Medica, 2018)
Cardamonin exhibits a variety of pharmacological activities including anti-inflammatory and antitumor, which are correlated with the inhibition of nuclear factor-kappaB and the mammalian target of rapamycin, respectively. However, whether the anti-inflammatory effects of cardamonin are mediated by the mammalian target of rapamycin remains unknown. In this study, ovarian cancer SKOV3 cells were cultured with lipopolysaccharide to induce inflammation, and the inhibitory effects and underlying molecular mechanisms of cardamonin were investigated using specific inhibitors of the mammalian target of rapamycin and the nuclear factor-kappaB pathway (rapamycin and pyrrolidine dithiocarbamate, respectively). Our results indicated that cardamonin inhibited the viability of normal and lipopolysaccharide-pretreated SKOV3 cells in a concentration-dependent manner. In accordance with rapamycin, the activation of the mammalian target of rapamycin and its downstream target, ribosomal protein S6 kinase 1, was inhibited by cardamonin, while pyrrolidine dithiocarbamate substantially blocked nuclear factor-kappaB activation and mildly inhibited the phosphorylation of the mammalian target of rapamycin and ribosomal protein S6 kinase 1. Pretreated with pyrrolidine dithiocarbamate, the effect of cardamonin on the mammalian target of rapamycin signalling was not affected, but the expression of inflammatory factors was further reduced. In cells pretreated with rapamycin, the inhibitory effects of cardamonin were completely suppressed with regards to the phosphorylation of the mammalian target of rapamycin, ribosomal protein S6 kinase 1, TNF-α, and interleukin-6, and nuclear factor-kappaB p65 protein expression was decreased. In conclusion, our findings indicate that the anti-inflammatory effects of cardamonin are correlated with mammalian target of rapamycin inhibition.
Keywords: cardamonin; inflammation; lipopolysaccharide; mTOR; NF-κB; ovarian cancer